Prospek Pengembangan Pembenihan Ikan Lele (Clarias sp.) di Desa Babakan Kecamatan Ciseeng Kabupaten Bogor - Asep Korlan Dedi; Ani Suryani; Eko Ruddy Cahyadi (Institut Pertanian Bogor, 2015)
In the last five years the seed needs catfish are always increasing, yet able to be met by existing production. The objectives of research are as follows: (1) To obtain information on the feasibility business of catfish hatchery in Babakan village, (2) To identify internal and external factors that influence toward catfish hatchery development in Babakan and (3) To provide the alternative strategy for catfish hatchery development in Babakan. The criteria of the business feasibility analysis used in this study are Net Present Value (NPV), Net Benefit Cost Ratio (Net B/C), Internal Rate of Return (IRR), Break Even Point (BEP), and Payback Period (PBP). While the factors that influence toward business development are identified using Internal Factor Evaluation (IFE) matrix, External Factor Evaluation (EFE) matrix, Internal External (IE) matrix, and Strengths, Weaknesses, Opportunities, and Threats (SWOT) matrix. Lastly the Quantitative Strategic Planning Matrix (QSPM) is applied to provide an alternative strategy of business development. The results of the non-financial feasibility analysis showed that the catfish hatchery business in Babakan is still weak on the whole non-financial aspects. Based on the results of a financial feasibility analysis with the feasibility criteria and assumptions which have been determined, it is known that the catfish hatchery business of 7 fish farmers is feasible with 100%. The entire value of the NPV is greater than zero between International Drawing Right (IDR) 3.395.841 and IDR 53.262.759. The entire value of IRR is greater than the interest rate (14%) between 28,31% and 45,25%. The entire value of Net B/C is greater than 1 between 1.30 and 1.62. The entire value of the PBP is less than 3 years between 1.8 years and 2.3 years. Based on the result of both IE and SWOT analysis, of 7 fish farmers in Babakan that the catfish hatchery need to defend, develop and undertake progressive strategies. The best alternative strategy of business development business that recommended from QSPM analysis is the application of Good Hatchery Practices (CPIB) to increase production and quality of seeds, so that minapolitan program is reachable.